Flow properties of powdery or granular filling substances of dangerous goods packagings—Comparison of the measurement of the angle of repose and the determination of the Hausner ratio. Issue 10 (15th July 2022) - Schlick‐Hasper, Eva; Bethke, John; Vogler, Nico; Goedecke, Thomas
Abstract : To ensure safety when transporting dangerous goods, it is important to specify the flow properties of the respective solid filling substance of the packagings. For this purpose, the angle of repose is currently used for the UN approvals in Germany. Measurements were carried out on 12 powdery or granular substances applying the angle of repose measuring methods customary in the test centres. The results of the methods differ significantly from each other. In addition, some of the techniques cannot be applied for very cohesive or coarse‐grained materials. The results for the angle of repose show a strong scatter for some constellations (coefficient of variation more than 20%). Safety during transport of dangerous goods cannot be guaranteed with this currently practised system of measuring the angle of repose. As a consequence, an alternative parameter to characterize the flow properties of bulk materials should be used in the recognized test centers for dangerous goods packagings, such as the Hausner ratio. This approach leads to more precise test results for the substances examined (maximum coefficient of variation 2.8%). It also has advantages in terms of applicability and occupational safety. Since the flow properties are safety‐relevant, both in terms of mechanical safety and safety against the release of dangerous substances, the testing practice in the recognized test labs should be improved and standardized. Abstract : To ensure safety when transporting dangerous goods, it is important to specify the flow properties of the solid filling substance of the packagings. The results for the angle of repose obtained by different methods show a strong scatter for some of the 12 substances investigated (coefficient of variation more than 20%). The application of the Hausner ratio leads to more precise results (maximum coefficient of variation 2.8%). The testing practice in the recognized test labs should be improved and standardized.